A study on testing approach for mobile application testing / Siti Hafizah Zainol Abidin - Zainol Abidin, Siti Hafizah (2017)
Mobile application testing is more challenging than testing web application on desktop due to several factors. These factors are different range of mobile devices with different screen sizes and hardware configurations, wide varieties of mobile devices, different mobile operating systems, and also different version of operating system. Furthermore, different issues on complexity of measuring quality areas and selection of test tool and appropriate test approach. The main aim of this research is to study test approach for mobile application testing based on current industry best practices and international software testing standard applied in two (2) organizations in Malaysia. There are two objectives in this research. The first objective is to identify appropriate test approach for mobile application testing based on current industry best practices and second objective is to recommend the employment of test measurement in mobile application testing. This research utilized mainly qualitative method in collecting data from experts and practitioners. The qualitative methods that have been chosen for this research is interview with the practitioners and experts with related field in mobile application testing. For the finding, researcher is summarized in the recommendation on appropriate test approach for mobile application testing. It also determined the limitation of the test approach and future recommendation towards improvise the test approach in current industry best practice.